2016
DOI: 10.1007/s00134-016-4594-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early postextubation high-flow nasal cannula vs conventional oxygen therapy on hypoxaemia in patients after major abdominal surgery: a French multicentre randomised controlled trial (OPERA)

Abstract: Among patients undergoing major abdominal surgery, early preventive application of high-flow nasal cannula oxygen therapy after extubation did not result in improved pulmonary outcomes compared with standard oxygen therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
155
3
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 165 publications
(172 citation statements)
references
References 29 publications
3
155
3
11
Order By: Relevance
“…It has been reported to improve oxygenation after extubation in infants [12]. One clinical study indicated that HFNC might have benefit in patients with abdominal surgery [13]. However, after two years of research, they failed to identify beneficial effect of HFNC therapy after extubation in terms of the reduction of either reintubation or NIV application.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to improve oxygenation after extubation in infants [12]. One clinical study indicated that HFNC might have benefit in patients with abdominal surgery [13]. However, after two years of research, they failed to identify beneficial effect of HFNC therapy after extubation in terms of the reduction of either reintubation or NIV application.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective RCTs in both the ICU and the postoperative period have found that HFNC is non-inferior to NIPPV in terms of preventing respiratory failure but is better tolerated in terms of patients’ comfort 120121. One of the largest trials to examine the potential role for HFNC in preventing postoperative respiratory failure is OPERA, in which 220 post-abdominal surgery patients were randomized to receive either HFNC or standard oxygen therapy 122. No significant differences were found between groups in the absolute reduction in risk of hypoxemia or in the incidence of PPCs.…”
Section: Additional Considerationsmentioning
confidence: 99%
“…In another study, the preventive application of NHF directly after extubation was compared to SOT in patients undergoing major abdominal surgeries. NHF was ineffective at reducing the incidence of hypoxaemia as well as other postoperative outcomes such as pulmonary complications and length of hospital stay [54]. The small sample size, along with the lower than expected rate of hypoxaemia after surgery might have influenced the results, and thus more studies are needed to clarify the role of NHF after abdominal surgery.…”
Section: No Benefitmentioning
confidence: 98%